S69 Implementation of a COPD discharge care bundle and hospital readmissions in london. (14th November 2013) - Laverty, AA; Elkin, S; Watt, H; Williams, S; Restrick, L; Bell, D; Hopkinson, NS
Abstract : Background: Acute exacerbations of COPD (AECOPD) are a major cause of morbidity, mortality and hospital admissions. Audit data shows significant variation in delivery of evidence-based interventions and readmission rates suggesting that optimising the care process may be beneficial. One approach is the "care bundle" where a series of evidence-based interventions which should be delivered for all patients is mandated, irrespective of ward, or specialty, delivering care. A COPD discharge care bundle was developed by the NIHR CLAHRC for Northwest London [Hopkinson et al 2012] and has been adopted by a number of acute hospitals in London, incentivised in some by commissioners using the Commissioning for Quality and Innovation (CQUIN) payment framework. Methods: To provide initial information on use of the bundle and readmissions we performed a Negative Binomial regression interrupted time series analysis comparing 7, 28 and 90 day readmission rates in hospitals before and after bundle adoption. The bundle was implemented at various time points between 2009 and 2011 in 9 Trusts in London, comprising 15 hospitals. Data from April 2002 to March 2012 were obtained from Hospital Episode Statistics using COPD exacerbation codes - J440 & J441 in the first position. Results were controlled for seasonality using month of admission and were also controlled for age and sex of patients at Trust level. Results: Following implementation of the COPD discharge bundle there was a significant change in the trend for the 28-day readmission rates for patients discharged after AECOPD. Falls were also indicated for 7- and 90-day readmissions, although these were not statistically significant at p < 0.05. Conclusion: These data suggest that the care bundle approach may be one systematic way to improve outcomes in patients admitted with an AECOPD. More work is needed, however, to separate any effects of the care bundle from other initiatives, e.g. Local Enhanced Services, that support delivery of evidence-based care in COPD i.e. quit-smoking interventions and pulmonary rehabilitation.